Essays in financial markets - Steen Nielsen (Copenhagen Business School (CBS), 2000)
This dissertation adresses various issues regarding the functioning of financial markets. It consists of introduction and five independent chapters of which the first four are empirical and the last one is theoretical. The introduction provides a brief background on some of the data used in subsequent chapters and a discussion of the main results of the dissertation
hdl:10398/7935
Keywords: 650